The Drug War and Regional Social Capital in Mexico - Julian-Ferdinand Vögele; Fabian Reck; Jarko Fidrmuc (Journal of International Development, 2023)
The onset of the war on drugs in Mexico at the beginning of 21st century had far-reaching effects on its citizens, including most obviously, an unprecedented increase in the homicide rate. We analyse the correlation between violence on social capital in the 32 federal states of Mexico from January 2004 to December 2016. Given the lack of data in the conflict regions of Mexico, we apply the indirect approach proposed by Guriev and Melnikov (2016), which uses internet search engine data to proxy social capital. Our results show a negative relationship between violence and social capital in Mexico. Moreover, we document a positive spatial correlation for social capital. Overall, we present an example of how the analysis of internet-based data can contribute to the understanding of socioeconomic developments in conflict regions with unreliable standard data.
Keywords: 300; drug war; social capital; violence